2017
DOI: 10.1155/2017/2861596
|View full text |Cite
|
Sign up to set email alerts
|

Plasmablastic Lymphoma with Coexistence of Chronic Lymphocytic Leukemia in an Immunocompetent Patient: A Case Report and Mini-Review

Abstract: Background Plasmablastic lymphoma (PBL) is a rare, aggressive B-cell lymphoma with poor prognosis usually found in the oral cavity of HIV-positive patients. Chronic lymphocytic leukemia (CLL) is an indolent B-cell lymphoma with a variable clinical course. Transformation of CLL to PBL as Richter's syndrome is rare while coexistence of CLL and PBL at diagnosis is even rarer. Case Report We describe a case of a male immunocompetent patient with an ileum-cecum valve mass and a soft tissue mass at the left humerus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…The concomitant occurrence of PBL with other types of lymphoma is extremely rare. Review of the English literature revealed only six case reports in which the histopathological findings of two lymphomas were described [9][10][11][12][13][14]. The clinicopathological features of these previous cases and the present case are summarized in Table 1.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…The concomitant occurrence of PBL with other types of lymphoma is extremely rare. Review of the English literature revealed only six case reports in which the histopathological findings of two lymphomas were described [9][10][11][12][13][14]. The clinicopathological features of these previous cases and the present case are summarized in Table 1.…”
Section: Discussionmentioning
confidence: 82%
“…R-CHOP was selected for the present case, similar to a previous case of concurrent DLBCL and PBL that showed recurrence of DLBCL after 4 years [9]. Other cases of PBL co-existing with CLL/SLL were also refractory to R-CHOP and/or vincristine, adriamycin, and dexamethasone (VAD) treatment (Table 1, cases 1-5) [10][11][12][13][14]. Basically, standard treatment for PBL has not been established due to the rarity of the disease and its aggressive clinical course.…”
Section: Discussionmentioning
confidence: 99%
“…None of the patients had a known history of immunodeficiency. Three cases had both CLL and PBL diagnosed simultaneously [2, 10, 11], whereas for the remaining 12 cases, the time between CLL diagnosis and PBL diagnosis varied from 14 to 132 months. Four patients had received prior treatment with Ibrutinib for a duration of 18–96 months before developing plasmablastic lymphoma.…”
Section: Figurementioning
confidence: 99%
“…A review of the literature on PBL arising in the context of CLL yielded 15 cases [2,[7][8][9][10][11][12][13][14][15][16], the findings of which are summarized in and a 17p13.1 deletion, along with a TP53 mutation. 14 In two cases, FISH analysis was performed for BCL2, BCL6, CCND1, MYC and TP53 abnormalities in both the CLL and PBL.…”
mentioning
confidence: 99%
“…As previously mentioned, CLL is a very heterogenous B cell malignancy with a wide range of behaviors from patient to patient. Since 1928, a very aggressive and invasive form of lymphoma derived from CLL, named Richter's syndrome (RS) has been described [76][77][78][79]. A recent work has analyzed the circulating EVs in both CLL and RS patients and discovered high levels of miR-19b as predictor of the evolution of drug-resistant CLL toward RS, resulting in down-regulation of TP53 and up-regulation of MKI67, as mechanism of tumor cell proliferation, survival and invasion [80].…”
Section: Mirnas Of Cll-derived Exosomes Modify the Tumor Microenvironmentioning
confidence: 99%